The Effect Of Store Atmosphere On Purchase Decisions At Chirurgie Cafe And Books Medan - Pramesco Wiranta Sembiring (IHSA Institute, 2021)
This research is motivated by the importance of store atmosphere in a cafe or shop, because now the price, discount, promotion and service do not become guarantee of consumer to make a purchase, but store atmosphere (good store atmosphere) will be the main attraction for cafe Who own it, so as to attract consumers to make a purchase.The purpose of this research is to know the influence of store exterior, general interior, store layout and interior display to purchase decision at Chirurgie Cafe and Books Medan.This research uses quantitative method with associative approach. The population in this study were all visitors of Chirurgie Cafe and Books Medan with sample size 100 people. The sampling technique in this research is done by using Non Probability Sampling technique with accidental sampling technique and purposive sampling. Analytical methods used are validity test, reliability test, t-test, f-test, classical assumption test, multiple linear regression analysis test, and coefficient of determination (R2) test.The result of this research shows that partially the result of store exterior variables is tcount (1,728)> ttable (1,6608) and probability value 0,087 <0,1, which means that store exterior (X1) has positive and significant effect to purchasing decisions). The general interior variables show that tcount (2.234)> ttable (1.6608) and probability value 0.028 <0.1, which means that general interior (X2) has positive and significant effect to purchase decision (Y). The store layout variable shows that tcount (2.2072)> ttable (1.6608) and probability value 0.041 <0.1, which means that store layout (X3) has positive and significant effect on purchase decision (Y). Exterior store variables show that tcount (0.397)> ttable (1.6608) and probability value 0.692 <0.1, which means that interior display (X4) has positive but not significant effect on purchasing decision (Y). Simultaneously the independent variable (free) shows that the fcount is 7.011 with the significance level 0.000, while the ftable at the 90% confidence level (α = 0.10) is 2.00. Then fcount (7.011)> ftable (2.00) and probability value 0.000 <0.10, which means all independent variables simultaneously affect the dependent variable.